Harms Of Loot Boxes And Approaching Regulation In Singapore - Jiow, Hee Jhee; Lim, Jun Ming (Loading, 2021)
‘Loot boxes’ are a type of videogame monetization model that contains randomized rewards of varying rarities which emerged in recent years. The element of chance seeks to entice players into buying loot boxes in hopes of receiving a rare and desirable reward. The design of loot boxes has been identified to be addictive and to entice players to spend more money than they estimate they would. With links to addiction and gambling behaviours, loot boxes may cause social harm if unregulated. Singapore is not new to the videogaming scene and may seek to regulate loot boxes should it emerge as a social problem amongst Singaporeans. By acknowledging existing approaches towards regulating loot boxes and situating loot boxes in Singapore’s social context, this paper explores Lessig’s four modalities of constraint as a framework to hypothesize regulatory options for Singapore.